Parámetros de diseño de sistema de osmodeshidratación del yacón a partir de sus parámetros de proceso. - Bocanegra Díaz, Juan Julio (2013)
The present study had as purpose to determine the parameters of design of an osmotic dehydration of yacon system from their process parameters: temperature, concentration and time. The testing of pilot scale was carried out in a marmite of one litter. This marmite was built by stainless steel, adequate to a heating system with steam and solenoid coils in order to immerse the raw material. It was evaluate mass transfer during osmotic dehydration of yacon cubes of 2 cm of edge, using two temperatures (30°C and 40°C) and three concentrations of hypertonic solution of fructooligosaccharides (50, 60 and 70° Brix). The study of the kinetics of the osmotic dehydration was carried out for 48 hours, which evaluated water loss and gain in solute. The values of coefficients of effective diffusion of the water obtained are found from 8, 87 x 10-7 m2/s to 1, 06 x 10-6 m2/s, using the model proposed by Azuara et al, based on the second equation of Fick. The result showed that the treatment with 60°Brix and 30°C had the highest value of water loss (54,57%) and higher value of effective diffusivity (9, 89 x 10-7 m2/s). The design parameters of the osmotic dehydrator (steam pressure entering the jacket, steam flow required, area and thickness of the jacket) were determined by the operating parameters (60°Brix y 30°C).The program requires as an input: the initial temperature, the temperature of dehydration, the flow of material to be dehydrated, cylinder diameter, fruit- syrup ratio, osmotic liquid density and density of the product.